COVID-19 poses grievous economic challenge to landlocked developing countries - United Nations (United Nations Department of Economic and Social Affairs, 2020)
The thirty-two landlocked developing countries (LLDCs) — home to nearly 7 per cent of world population, repre¬senting 15 per cent of the membership of the United Na¬tions—are the least economically-integrated countries in the world. As a group, LLDCs are at the fringes of the world economy, accounting for only 0.9 per cent of world gross output and 0.8 per cent of global exports (Figure 1). Seventeen of them also belong to the group of least de¬veloped countries (LDCs). These economies are highly heterogeneous, both in terms of the level of development and economic structure. The average per capita income of LLDCs is 2.5 times higher than the LDC average. This average, however, masks the huge dispersion in per capi¬ta income among these countries, ranging from $272 for Burundi to $9,813 for Kazakhstan.
Article
Keywords: Landlocked developing countries; Economic challenge; COVID 19